2011
DOI: 10.1007/s12072-010-9243-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo combination of lamivudine and adefovir versus entecavir monotherapy for the treatment of naïve HBeAg-negative chronic hepatitis B patients

Abstract: Purpose Either combination treatment or monotherapy using agents with a high genetic barrier are recommended for hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB). The aim of this study was to compare effect of naïve HBeAg-negative CHB patients with either de novo combination of lamivudine (LAM) and adefovir dipivoxil (ADV) or entecavir (ETV) monotherapy. Methods HBeAg-negative CHB patients (n = 71) with ALT levels between 2 and 10 times the upper normal limit and HBV DNA levels [10 4 copies/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Nearly 60.0% of patients with HBV DNA ≥10 8 copies/ml in the ETV group had a virological response by week 52, and >80% of patients in the ETV group who had cirrhosis at baseline achieved a virological response. The efficacy and safety data for ETV in this study are consistent with results from global and Chinese clinical trials with ETV [7,8,13]. A large observational study conducted in China in 2013 reported similar virological responses with ETV in NUC-naive patients (69%) and in those with cirrhosis (64-68%) after a 48-week treatment period [14].…”
Section: Discussionsupporting
confidence: 85%
“…Nearly 60.0% of patients with HBV DNA ≥10 8 copies/ml in the ETV group had a virological response by week 52, and >80% of patients in the ETV group who had cirrhosis at baseline achieved a virological response. The efficacy and safety data for ETV in this study are consistent with results from global and Chinese clinical trials with ETV [7,8,13]. A large observational study conducted in China in 2013 reported similar virological responses with ETV in NUC-naive patients (69%) and in those with cirrhosis (64-68%) after a 48-week treatment period [14].…”
Section: Discussionsupporting
confidence: 85%
“…Based on the paradigm that a drug combination is more effective than monotherapy for the treatment of human immunodeficiency virus (HIV), the same approach may be appropriate for chronic hepatitis B. Few studies have assessed combination therapy in chronic hepatitis B [12,15,16]. From those studies, it was shown that de novo combination therapy with LAM and ADV was better than add-on combination therapy in terms of changes in Child-Pugh score, viral inhibition, and renal function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Both LAM +ADV combination therapy and ETV monotherapy are effective in naïve HBeAg-negative CHB patients [12]. However, it is unclear whether the combination of LAM and ADV is effective in HBeAg positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…In certain clinical settings, including LAM failure and post-liver transplant status, combination therapy has been found to improve long-term efficacy of viral suppression 41. Although no large trials have been completed yet, the combination of ADV and LAM, given de novo, has compared favorably to LAM monotherapy and even been shown to be as good as ETV in achieving virological and biochemical response 41,42. Given that the largest study involved only 71 patients (31 LAM plus ADV, 40 ETV) and treatment duration was only 48 weeks, larger studies over longer periods of time are needed.…”
Section: Reducing Risk Of Lam Anti-hbv Resistancementioning
confidence: 99%